Technology Acceptance Model Factors: Implications on Digital-Wallet on Interest to Buy in Franchise Business - Ida Farida; Wawan Ardiansyah (Manunggal Halim Jaya, 2022)
This study aimed to determine the effect of perceived usefulness and perceived ease of use of digital wallets on buying interest in the franchise in Bone Regency. The type of research used is quantitative research—data analysis techniques using multiple linear regression analysis accompanied by T-test and F-test. The calculation process uses SPSS 23. The test results are based on the F-test of perceived usefulness, and perceived ease of use of digital wallets influences buying interest because the significant value is smaller than 0.05. Then, based on the T-test of the perceived usefulness of digital wallets on buying interest, because the significant value is smaller than 0.05 (0.000 <0.05), the variable perceived ease of use of digital wallets does not affect purchase stake because the significant value is greater than 0.05 (0.638 > 0.05). So only perceived usefulness is very influential on buying interest in franchises in Bone Regency, South Sulawesi Province, Indonesia. Based on the results and discussion of the research that has been described, the researchers would like to suggest that Franchise companies reconsider the aspects of Perceived Usefulness and Perceived Ease of Use to increase consumer buying interest so that the company can survive during business competition.